2004
DOI: 10.1074/jbc.m401637200
|View full text |Cite
|
Sign up to set email alerts
|

240s Loop Interactions Stabilize the T State of Escherichia coli Aspartate Transcarbamoylase

Abstract: Here the functional and structural importance of interactions involving the 240s loop of the catalytic chain for the stabilization of the T state of aspartate transcarbamoylase were tested by replacement of Lys-244 with Asn and Ala. For the K244A and K244N mutant enzymes, the aspartate concentration required to achieve halfmaximal specific activity was reduced to 8.4 and 4.0 mM, respectively, as compared with 12.4 mM for the wild-type enzyme. Both mutant enzymes exhibited dramatic reductions in homotropic coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…22 The PreTS conformation is stable only in the presence of Mg 2+ ·ATP (and Trp), suggesting that it is comparable to the "relaxed" states of well-studied allosteric proteins like hemoglobin, 23,24 aspartate carbamoyl transferase, [25][26][27][28][29] and glycogen phosphorylase. 30,31 In keeping with this notion, interactions between TrpRS and ATP are far more optimal in the PreTS state than in the Open state.…”
Section: Discussionmentioning
confidence: 95%
“…22 The PreTS conformation is stable only in the presence of Mg 2+ ·ATP (and Trp), suggesting that it is comparable to the "relaxed" states of well-studied allosteric proteins like hemoglobin, 23,24 aspartate carbamoyl transferase, [25][26][27][28][29] and glycogen phosphorylase. 30,31 In keeping with this notion, interactions between TrpRS and ATP are far more optimal in the PreTS state than in the Open state.…”
Section: Discussionmentioning
confidence: 95%
“…The unit cell dimensions of the crystals of ATCase grown at pH 8.5, in the H3 space group, T high_apo , ( a = b = 129.78 Å, c = 197.74 Å) are similar to the unit cell dimensions of the few other T‐state crystals of ATCase in the H3 space group. Two of these structures in the H3 space group are of the wild‐type enzyme with substrates or substrate analogs in the active site (PDB entries: 1ROC24 and 2AIR40), whereas two were for the P268A (PDB entry 1EZZ41) and the K244N (PDB entry 1SKU32) mutant versions of ATCase in the absence of substrates or substrate analogues. The similarity of the unit cell dimensions of the T high_apo crystals reported here, as compared with these known T‐state structures in the same space group grown at pH values of seven or less, suggested that the crystals grown at pH 8.5 were in the T‐quaternary structure.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of the unit cell dimensions of the T high_apo crystals reported here, as compared with these known T‐state structures in the same space group grown at pH values of seven or less, suggested that the crystals grown at pH 8.5 were in the T‐quaternary structure. Therefore, the initial model used for the refinement of the structure was the T‐state structure of the K244N mutant ATCase in the H3 space group (PDB code 1SKU) 32. The data for the T high_apo were refined to a R factor and R free of 21.5% and 24.7%, respectively, with 213 water molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a and 5b). The importance of this interaction for the allosteric transition has been evaluated and described previously (Alam et al, 2004).…”
Section: Quality Of the Structure Of Aspartate Transcarbamoylase Mutantsmentioning
confidence: 99%